A smartphone-based approach to understanding how dementia risk factors relate to cognitive impairment - Rosická, Anna Marie (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2025)
As populations age and dementia prevalence increases, promoting brain health has become more important than ever before. Non-modifiable factors such as age, genes, and sex affect the risk of dementia, but they are not fully deterministic. Estimates suggest that almost a half of dementia cases worldwide could be prevented or delayed by reducing a range of potentially modifiable risk factors throughout life, and researchers are increasingly recognising the importance of understanding the factors that shape cognitive functioning pre-dementia, across the lifespan. This could enhance early detection of at-risk individuals and offer insight into the aetiology of dementia. The current thesis aimed to explore novel, smartphone-based cognitive measures as a tool for assessing and studying brain health and its antecedents. The first study validated a gamified cognitive task as a measure of visual working memory. The following three studies then used this task together with other smartphone-based cognitive measures to understand how dementia risk factors relate to cognitive impairment. Using data collected with a smartphone application, both in-person and remotely, this thesis found that subjective cognition was more closely linked to a range of previously established modifiable dementia risk factors across the lifespan compared to objective cognition, but neither subjective nor objective cognition was affected by a genetic risk factor for Alzheimer's disease in middle-aged adults. Additionally, a multivariate machine-learning analysis in a large lifespan sample showed that the individual differences contributing to cognition did not differ between men and women. The current thesis reviewed these findings and their implications in the context of the early detection of cognitive decline. Together, these results showcase smartphones as a promising platform for scaling up cognitive assessments both in research and in clinical settings. However, methodological, practical, and ethical limitations of this approach need to be considered.
APPROVED
Keywords: smartphone research; modifiable dementia risk factors; cognitive assessment; subjective cognition; sex differences; cognitive impairment; gamified cognitive tasks; brain health; machine learning